A commentary on Pseudo-Philo's Liber antiquitatum biblicarum, with Latin text and English translation - Jacobson, Howard, 1940- (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1996)
One of the earliest and most important works of biblical interpretation is a Latin text that is commonly known as the Liber Antiquitatum Biblicarum . It was written in the first second century C.E. and is thus a great source of illumination for the period and milieu out of which arose various Jewish sects and Christianity. This book offers the Latin text of LAB, a dramatically new translation, a commentary that deals extensively with LAB's place in ancient biblical exegesis, and an introduction that treats the major problems associated with LAB (e.g. date, original language, manuscript tradition, exegetical techniques). The author seeks to illuminate LAB in new ways by reconstructing the original Hebrew when that is useful, and by bringing new and pertinent evidence from the Bible, from Rabbinic literature, and from early Christian literature.